HIPS: evaluating a virtual reality training simulation for total hip arthroplasty (THA) and insights into qualitative assessment of surgical training simulations - Lorenz, Mario; Knopp, Sebastian; Pillen, Nina; Sanrow, Magdalena; Hoffmann, Andrea; Stoiser, Viktoria; Schmidt, Dennis; Atze, Johannes P. G.; Dettmann, André; Bullinger, Angelika C.; Zajonz, Dirk (Frontiers in Virtual Reality, 2025)
Surgery is a craft that has been handed down in a master–apprentice manner via supervised surgeries that demonstrates the need for high-quality training simulators. Despite advancements in this area, little progress has been made for one of the most common surgeries: total hip arthroplasty (THA). In this work, we describe a multiuser virtual reality training simulator for THA called HIPS that covers the surgical steps from cutting off the femoral head to insertion of the stem. This encompasses the simulation environment, surgical errors detected, multiuser capabilities, as well as user guidance and user feedback methods. In a mixed-method evaluation (N = 12), HIPS was deemed to be realistic, enjoyable, and needed in resident training. The qualitative evaluation methods used herein reveal valuable feedback for further improvements and important learnings for general assessment of surgical training simulators. The variations in surgical techniques need to be evaluated further at different hospitals in different countries along with high-quality simulations of all sensory cues.